2022
DOI: 10.1002/advs.202105223
|View full text |Cite
|
Sign up to set email alerts
|

A Vehicle‐Free Antimicrobial Polymer Hybrid Gold Nanoparticle as Synergistically Therapeutic Platforms for Staphylococcus aureus Infected Wound Healing

Abstract: Pathogenic bacteria infection is a serious threat to human public health due to the high morbidity and mortality rates. Nano delivery system for delivering antibiotics provides an alternative option to improve the efficiency compared to conventional therapeutic agents. In addition to the drug loading capacity of nanocarriers, which is typically around 10%, further lowers the drug dose that pathological bacteria are exposed to. Moreover, nanocarriers that are not eliminated from the body may cause side effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 43 publications
0
58
0
Order By: Relevance
“…Many studies have revealed that transformation of the macrophage phenotype is the central regulatory contributor that orchestrates the transitions among all phases of wound healing [ 6 ]. In the normal wound microenvironment, macrophages exhibit a pro-inflammatory phenotype (M1) during the early stage and then shift to an anti-inflammatory phenotype (M2) during the later stage [ 7 ]. However, macrophages maintain a pro-inflammatory M1 phenotype in chronic diabetic wounds due to the presence of AGEs and secrete pro-inflammatory cytokines to sustain inflammation by recruiting new macrophages to the wound site and polarizing them to the M1 phenotype in a positive feedback loop [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that transformation of the macrophage phenotype is the central regulatory contributor that orchestrates the transitions among all phases of wound healing [ 6 ]. In the normal wound microenvironment, macrophages exhibit a pro-inflammatory phenotype (M1) during the early stage and then shift to an anti-inflammatory phenotype (M2) during the later stage [ 7 ]. However, macrophages maintain a pro-inflammatory M1 phenotype in chronic diabetic wounds due to the presence of AGEs and secrete pro-inflammatory cytokines to sustain inflammation by recruiting new macrophages to the wound site and polarizing them to the M1 phenotype in a positive feedback loop [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the changes of wound in ammation in rats were observed by tissue immuno uorescence staining. In the process of wound healing, there are two types of macrophages, proin ammatory (M1) and anti-in ammatory (M2) macrophages 45,46 , whose markers change to a certain extent. Wound in ammation can be assessed indirectly by investigating corresponding markers in tissue.…”
Section: Resultsmentioning
confidence: 99%
“…He et al forged an antimicrobial polymer polyhexamethylene biguanide (PHMB) hybridized with gold nanoparticles (Au NPs) platform (PHMB@Au NPs). PHMB@Au NPs exhibit superior synergistic effect to enhance both photothermal bactericidal effect under NIR irradiation and tissue repair by converting macrophages from M1 type to M2 type (He et al, 2022). The mechanisms and period of action of the various treatments are summarized in Table 3.…”
Section: Combined Immunotherapymentioning
confidence: 99%